Structural characterization and pharmacological evaluation of the new synthetic cannabinoid CUMYL‐PEGACLONE. Issue 3 (9th August 2017) - Angerer, Verena; Mogler, Lukas; Steitz, Jan‐Patrick; Bisel, Philippe; Hess, Cornelius; Schoeder, Clara T.; Müller, Christa E.; Huppertz, Laura M.; Westphal, Folker; Schäper, Jan; Auwärter, Volker
Abstract : The number of new psychoactive substances (NPS) that have emerged on the European market has been rapidly growing in recent years, with a particularly high number of new compounds from the group of synthetic cannabinoid receptor agonists. There have been various political efforts to control the trade and the use of NPS worldwide. In Germany, the Act to control the distribution of new psychoactive substances (NpSG) came into force in November 2016. In this new act, two groups of substances were defined, the group "cannabimimetics/synthetic cannabinoids" covering indole, indazole, and benzimidazole core structures, and a second group named "compounds derived from 2‐phenethylamine." Shortly after, the first retailers of "herbal blends" promoted new products allegedly not violating the German NpSG. We describe the identification and structural elucidation of one of the first synthetic cannabinoids not being covered by the NpSG, 5‐pentyl‐2‐(2‐phenylpropan‐2‐yl)‐2, 5‐dihydro‐1 H ‐pyrido[4, 3‐ b ]indol‐1‐one. For isolation of the substance a flash chromatography separation was applied. The structure elucidation was performed using gas chromatography–mass spectrometry (GC–MS), gas chromatography‐solid state infrared spectroscopy (GC–sIR), liquid chromatography–electrospray ionization–quadrupole time of flight–mass spectrometry (LC–ESI–qToF–MS) and nuclear magnetic resonance (NMR) analysis. Additionally, binding affinity towards the cannabinoid receptors CB1 and CB2 and efficacy in a cAMP accumulation assay were measured, showing full agonistic activity and high potency at both receptors. The new compound bears a γ‐carboline core structure circumventing the German NpSG and the generic definitions in other national laws. As a semi‐systematic name for 2‐cumyl‐5‐pe ntyl‐ga mma‐c arbol in‐1‐one CUMYL‐PEGACLONE is suggested. Abstract : This article describes the identification and structural elucidation of a new synthetic cannabinoid, 5‐pentyl‐2‐(2‐phenylpropan‐2‐yl)‐2, 5‐dihydro‐1 H ‐pyrido[4, 3‐ b ]indol‐1‐one. Additionally, the affinity of the new substance towards the cannabinoid receptors CB1 and CB2 and the efficacy in a cAMP accumulation assay were measured. The new compound bears a γ‐carboline core structure not covered by most generic legislative definitions of synthetic cannabinoids and presumably acts as a full agonist at the cannabinoid receptors. CUMYL‐PEGACLONE is suggested as a semi‐systematic name for the compound.